Teenage Childbearing as an Independent Risk Factor for Stress Urinary Incontinence in American Women - Xie, Li; Yu, Zhuoyuan; Gao, Fei (Urology Journal, 2022)
Purpose: To evaluate the associations among teenage childbearing (Age at first birth<=19 years old) with later-life risk of stress and urgency urinary incontinence (SUI, UUI) in American women using nationally representative data from America. Materials and Methods: Data from the National Health and Nutrition Examination Survey (NHANES) from 2015 to 2018 were merged to include 2673 women. The question, “How old were you at the time of your first live birth?” was used to assess teenage childbearing. Urinary incontinence was ascertained by self-report. Multivariable logistic regression models were used to assess the association between teenage childbearing and urinary incontinence in American women, controlling for potential confounders. Results: Among the 2673 women with complete data, the prevalence of SUI was 27.3%, and the prevalence of UUI was 22.1%. Overall, 856 of female had given birth at or before the age of nineteen. Teenage childbearing was significantly associated with SUI (OR=1.9, 95%CI=1.5-2.3, p < 0.001), but teenage childbearing was not associated with UUI (OR=1.2, 95%CI=1.0-1.5, p = 0.0658). Conclusion: After controlling for known risk factors, teenage childbearing seems to be signif-icantly related to female stress urinary incontinence.